![image](https://tex.z-dn.net/?f=-x%5E%7B2%7D%20%2B2x%2B8%3D0%3C%2Fp%3E%3Cp%3E%5C%5Cx%5E%7B2%7D%20-2x-8%3D0%3C%2Fp%3E%3Cp%3E%5C%5CD%3D%28-2%29%5E%7B2%7D%20-4%2A1%2A%28-8%29%3D36%286%5E%7B2%7D%20%29%3C%2Fp%3E%3Cp%3E%5C%5Cx1%3D%5Cfrac%7B-%28-2%29-6%7D%7B2%2A1%7D%20%3D-2%3C%2Fp%3E%3Cp%3E%5C%5Cx2%3D%5Cfrac%7B-%28-2%29%2B6%7D%7B2%2A1%7D%20%3D4)
\\x^{2} -2x-8=0
\\D=(-2)^{2} -4*1*(-8)=36(6^{2} )
\\x1=\frac{-(-2)-6}{2*1} =-2
\\x2=\frac{-(-2)+6}{2*1} =4" alt="-x^{2} +2x+8=0
\\x^{2} -2x-8=0
\\D=(-2)^{2} -4*1*(-8)=36(6^{2} )
\\x1=\frac{-(-2)-6}{2*1} =-2
\\x2=\frac{-(-2)+6}{2*1} =4" align="absmiddle" class="latex-formula">
Ответ:x=-2, x=4